2023
DOI: 10.3390/v15051187
|View full text |Cite
|
Sign up to set email alerts
|

Detection of SARS-CoV-2 in Terrestrial Animals in Southern Nigeria: Potential Cases of Reverse Zoonosis

Anise N. Happi,
Akeemat O. Ayinla,
Olusola A. Ogunsanya
et al.

Abstract: Since SARS-CoV-2 caused the COVID-19 pandemic, records have suggested the occurrence of reverse zoonosis of pets and farm animals in contact with SARS-CoV-2-positive humans in the Occident. However, there is little information on the spread of the virus among animals in contact with humans in Africa. Therefore, this study aimed to investigate the occurrence of SARS-CoV-2 in various animals in Nigeria. Overall, 791 animals from Ebonyi, Ogun, Ondo, and Oyo States, Nigeria were screened for SARS-CoV-2 using RT-qP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Thus, continuous FHM cells can adsorb SARS-CoV-2 on their surface while maintaining its viability under certain conditions. The preservation of the infectious properties of SARS-CoV-2 in various types of water during this time has been shown for temperatures of 20-24 • C [45,67,68], which may be sufficient for the virus adsorption, for example, on the gill epithelium of some fish species. The results obtained show that the ability to adsorb SARS-CoV-2 is significantly higher in epithelial-like FHM cells compared to CGIB diploid fibroblasts, which may also be due to differences in the cell receptor apparatus and a greater presence of ACE2 on FHM.…”
Section: Sars-cov-2 Infection In Reptile Cell Culturesmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, continuous FHM cells can adsorb SARS-CoV-2 on their surface while maintaining its viability under certain conditions. The preservation of the infectious properties of SARS-CoV-2 in various types of water during this time has been shown for temperatures of 20-24 • C [45,67,68], which may be sufficient for the virus adsorption, for example, on the gill epithelium of some fish species. The results obtained show that the ability to adsorb SARS-CoV-2 is significantly higher in epithelial-like FHM cells compared to CGIB diploid fibroblasts, which may also be due to differences in the cell receptor apparatus and a greater presence of ACE2 on FHM.…”
Section: Sars-cov-2 Infection In Reptile Cell Culturesmentioning
confidence: 88%
“…SARS-CoV-2 infection of zebrafish larvae (Danio rerio) [43] and adults of three spot gourami (Trichopodus trichopterus) [44] did not lead to infection. Happi AN et al detected SARS-CoV-2 RNA in oral and cloacal swab samples of common agama (Agama agama) in two states of Nigeria in 2021-2022 [45]. Data on the study of the susceptibility of reptiles to SARS-CoV-2 in vivo and their cells in vitro are not available in accessible sources.…”
Section: Introductionmentioning
confidence: 99%
“…However, in Italy, Fiorito et al [ 28 ] reported 13/24 lactating cattle which were sampled on a single farm had neutralizing antibodies against SARS-CoV-2; the latter data are suggestive of transmission occurring within the herd. Interestingly, SARS-CoV-2 RNA was isolated from nasal and/or rectal swabs collected from cattle during the human Delta VOC wave of transmission in both India and Nigeria, suggesting Delta VOC susceptibility and recent exposure [ 27 , 30 ]. Together, these data support the conclusion that during the Delta VOC wave of transmission in humans, there were instances of spillover of SARS-CoV-2 Delta VOC from humans into cattle.…”
Section: Discussionmentioning
confidence: 99%
“…44,45 Current evidence suggests that SARS-CoV-2 has adapted to new mink and white tail deer hosts and at least some mink-associated novel variants are capable of spilling back to humans. 46 Although current evidence suggests that pigs 47,48,49,50,51,52,53 and cattle 54,55,56 are not routinely susceptible to infection with circulating strains of SAR-CoV-2, were SARS-CoV-2 strains to adapt to infect livestock, other circulating strains of enzootic coronaviruses in livestock might increase the risk of novel virus generation through recombination. When confronted with a patient with unexplained illness and negative diagnostic tests, clinicians are wise to ask questions about a patient's exposure to animals and to consider animal pathogen involvement in the patient's signs and symptoms.…”
Section: Figure 2 the Human Immune System Prevents Most Microbial Ass...mentioning
confidence: 99%